Media Pers dan Negara: Keluar dari Hegemoni - Siregar, Ashadi (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
The hegemony of the New Order state was established through the abusive use of press and moreover leave the press in a political inertia. The attempt to dismantle the hegemony shall rely on an understanding of the importance of establishing reciprocal relationship between the state and the citizen. Freedom of the press is meaningful to the state for securing its legitimacy and on the other hand opens up citizen participation in controlling the state.